Types of Violence and Character Responses in Lord of The Flies - Billa, Bagus Amantu (Journal of Literature, Linguistics, & Cultural Studies, 2024)
William Golding’s Lord of The Flies is a novel that contains violence in the story. The researcher chooses Golding’s Lord of The Flies as the object of the study because the violence that occurs in the novel portrays the worst side of humans. This study aims to find the kind of violence that occurs in the novel and the other character’s response to Jack’s violence in William Golding’s Lord of The Flies. This study uses Johan Galtung’s (1969, 1990) theory of violence, using his typology of violence which are Direct Violence, Structural Violence, and Cultural Violence. Therefore, as a result of this study, the researcher found that there are direct and indirect violence that occur in the novel Lord of The Flies. Direct violence is divided into two kinds: physical violence, and psychological violence (verbal and non-verbal). Indirect violence is structural violence and cultural violence. Most of the violence actions were done by Jack. The researcher also found the result of other characters response to Jack’s violence are Resistances and Supports to Jack’s Violence. Therefore, Then, the researcher suggests for further researcher who wish to use the same theories and approach as this thesis in analyzing William Golding’s Lord of The Flies can expand the discussion in more detail, especially in the other character’s response to Jack’s violence.